The Dean of the Faculty of IT & QS visits UiTMCS - Bohari, Zubaidah; Bujang Khedif, Lenny Yusrina (UiTM Sarawak, 2004)
The Dean Of the Faculty Of Information Technology & Quantitative Sciences, Prof Madya Dr. Azizi Ngah Tasir paid his last visit as the Dean of Faculty to our Campus on 30 December 2003, as part of a series of visits throughout the branch campuses. The purpose of the visit was to enable him to share his experiences and insights with the lecturers and the students of the faculty